Metal Complexes of Saccharin With the N-(2 Ligand: Synthesis, Characterization and Spectroscopic Examination. Crystal Structures of Trans-Bis(saccharinato)bis{n Copper(II) and Cadmium(II) - Yilmaz, V.T.; Karadaǧ, A.; Thoene, C. (Taylor & Francis Ltd, 2002)
The novel transition metal saccharinato complexes of N-(2-hydroxyethyl)-ethylendiamine (HydEt-en) have been synthesized and characterized by elemental analyses, magnetic moments, UV-Vis and IR spectra. Coordination behaviour of HydEt-en has been studied. The Mn(II), Ni(II), Cu(II), Zn(II), Cd(II) and Hg(II) form mononuclear complexes, while the Fe(II) and Co(II) complexes are dimeric. The crystal structures of the [Cu(sac)2(HydEt-en)2] and [Cd(sac)2(HydEt-en)2] complexes, where sac is the deprotonated form of saccharin, were determined by x-ray diffraction. The metal ions are octahedrally coordinated by these ligands. The amine ligand acts as a bidentate N-donor ligand and its ethanol group is not involved in coordination. The sac ions coordinate through the deprotonated N as a monodentate ligand. The NH and OH groups of the amine ligand are involved in intra- and intermolecular hydrogen bonding with the carbonyl and sulphonyl oxygens of the sac ions to form a three-dimensional infinite network.
Keywords: (2-Hydroxyethyl)-Ethylenediamine Complexes; Crystal Structures; Saccharin Complexes